2007
DOI: 10.1002/anie.200604844
|View full text |Cite
|
Sign up to set email alerts
|

Fiber Formation by Highly CO2‐Soluble Bisureas Containing Peracetylated Carbohydrate Groups

Abstract: Supercritical carbon dioxide (scCO 2 ) has attracted interest as an environmentally benign solvent, [1] but its practical usage is limited by the low CO 2 -solubility of polar and high-molecularweight compounds. To enhance the CO 2 -solubility of such compounds, CO 2 -philic surfactants, [2,3] dispersants, [4,5] thickeners, [6] and polymers [5,7] have been designed. Early success was achieved by the use of polyfluoroalkyl groups: various derivatives incorporating these groups showed enhanced CO 2 -solubility. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 26 publications
(1 reference statement)
0
24
0
2
Order By: Relevance
“…In four of the twelve compounds studied, the bis-urea was capable of dissolving in CO 2 without being heated and increasing the viscosity of CO 2 by factors of about 3-5 at concentrations of ~5wt% at 25 o C and 4,500 psia. In an attempt to design a non-fluorous analog of these expensive fluorous bis-ureas, CO 2 -philic hydrocarbon groups and CO 2 -philic carbonyl and ether groups were incorporated into the structure [Paik et al, 2007]. It was hoped that these compounds might also dissolve in CO 2 , self-assemble into long cylinders, remain in solution, and thicken CO 2 .…”
Section: Small Molecule Co 2 Thickenersmentioning
confidence: 99%
“…In four of the twelve compounds studied, the bis-urea was capable of dissolving in CO 2 without being heated and increasing the viscosity of CO 2 by factors of about 3-5 at concentrations of ~5wt% at 25 o C and 4,500 psia. In an attempt to design a non-fluorous analog of these expensive fluorous bis-ureas, CO 2 -philic hydrocarbon groups and CO 2 -philic carbonyl and ether groups were incorporated into the structure [Paik et al, 2007]. It was hoped that these compounds might also dissolve in CO 2 , self-assemble into long cylinders, remain in solution, and thicken CO 2 .…”
Section: Small Molecule Co 2 Thickenersmentioning
confidence: 99%
“…Out of the 12 compounds tested, 4 fluorinated bis-urea compounds were highly soluble in CO 2 without needing heat and capable of improving the CO 2 viscosity by 3-5-fold at 5 wt% of bisurea at 298 K and 31 MPa. In the hope of obtaining a non-fluorous bis-urea, Paik et al [67] attempted to incorporate the CO 2 -philic groups (hydrocarbon, carbonyl, and ether groups) into the molecular structure of the bis-urea as illustrated in Figure 5. However, their results revealed that after forming a transparent solution, microfibres began to form slowly due to the molecules undergoing self-assembly Enhanced Oil Recovery Processes -New Technologies and precipitating out of solution.…”
Section: Fluorinated and Non-fluorinated Bis-ureasmentioning
confidence: 99%
“…For example, to synthesize peracetylated carbohydrate intermediates from D-glucamine without acetylating the amino group, Hamilton and coworkers utilized acetyl chloride under acidic conditions, which prevented acylation of the primary amine by formation of the ammonium chloride salt. 23 The field of carbohydrate chemistry has encouraged the development of strategies for the regioselective acylation of either primary or secondary hydroxyl groups. For example, modified 4-( N,N '-dimethylamino)pyridine (DMAP)- and peptide-based catalysts have been explored to selectively functionalize carbohydrates on their secondary hydroxyl groups.…”
Section: Chemoselective Transformation Of Hydroxyl Groups In Small Momentioning
confidence: 99%